1991
DOI: 10.1017/s0022215100115063
|View full text |Cite
|
Sign up to set email alerts
|

Foreign bodies in the throat: a prospective study of 388 cases

Abstract: We present the results of a prospective study of 388 patients presenting with a history of swallowing a foreign body. We indicate whether the patients' symptoms and signs were associated with a retained foreign body. While tenderness on palpation was an unreliable sign, pooling at indirect laryngoscopy invariably predicted a retained object. In many patients, initial careful examination of the oropharynx by casualty officers would have shown a retained fishbone in the tonsil or tongue and would have resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 15 publications
1
41
1
5
Order By: Relevance
“…In the pharyngoesophagus, the most common symptoms were dysphagia and foreign body sensation. Among the signs, odynophagia and pooling of saliva were most frequently associated with a retained foreign body [11].…”
Section: Discussionmentioning
confidence: 99%
“…In the pharyngoesophagus, the most common symptoms were dysphagia and foreign body sensation. Among the signs, odynophagia and pooling of saliva were most frequently associated with a retained foreign body [11].…”
Section: Discussionmentioning
confidence: 99%
“…Coins are the most common objects among children, whilst in adults oropharyngeal foreign bodies are usually fish bones [I]. Larger objects such as false teeth or dental plates have also been reported [2]. The unusual feature in our patient was that such a large foreign body caused so little upper airway irritation.…”
Section: Another Foreign Body In the Airwaymentioning
confidence: 67%
“…Although pathological study is necessary for a differential diagnosis, plain X-ray examination may be helpful in the diagnosis, especially for a radio-opaque foreign body. However, Jones et al [5] reported that plain X-ray films yield 35 percent false positives or negatives in patients presenting with a history of swallowing a foreign body. In the suspicion of a tongue neoplasm, MRI is a valuable diagnostic tool, which is especially helpful in differentiating between an inflammatory lesion and a neogrowth.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of objects have been reported, including fish bones [9], metallic material [2,3], pipes [11], teeth [1] and dental material [10]. In general, fish bones are the most common impacted foreign bodies in otolaryngology, being found mostly in the tonsil, soft palate, tongue base, vallecula, posterior pharyngeal wall and upper esophagus [5]. However, it is rare that a fish bone totally embedded in the mobile part of the tongue presents as an enlarged mass.…”
Section: Introductionmentioning
confidence: 99%